Out of this world - Dean, James, 1957- (New York, NY : Harper Festival, an imprint of HarperCollinsPublishers, 2017)
"When Pete heads off to space camp, he gets to float in zero gravity, build rockets, and even goes on an extraordinary interstellar mission that is out of this world--literally."--Amazon.com.
P-3.
Keywords: Pete, -- the Cat (Fictitious character) -- Juvenile fiction; Pete, -- the Cat (Fictitious character) -- Fiction; Cats -- Juvenile fiction; Science camps -- Juvenile fiction; Picture books for children